(untitled) (Fiep Bulletin - online, 2014)
Teachers in “special” content areas (Physical Education, Music etc.) often rely on their personal beliefs systems in order to achieve the desired curricular outcomes. These guide their actions and behaviors in class. Previous research showed that beliefs persisted during undergraduate students’ formal training (Doolittle et al., 1993; Matanin & Collier, 2003). The purpose of the present study was to examine the impact of the second academic year of the Faculty of Sport Science in Athens on the beliefs toward the desired curricular outcomes of PE students with a teaching or coaching orientation. The participants were 60 third year undergraduate students (21.32±0.70 years) from the Faculty of PE and Sport Science of Athens, of which 24 had teaching and 36 coaching orientation. They completed twice the Greek version of “Beliefs toward curricular outcome goals” scale, a previously validated instrument (Adamakis et al., 2012), at the end of their first and at the beginning of their third academic year. The scale consists of 4 desired outcomes, Physical activity and fitness (PA), Self-actualization (SA), Motor skills development (MS ) and Social development (SD). Data were analyzed using descriptive and inferential statistics (mixed design ANOV A). The 4 desirable outcome goals differed significantly [F(3,56)=50.04, p<.001], with the PA goal being the prevailing one, followed by SA, for both teaching and coaching oriented students [F(3,56)=.52, p=.67]. This result did not change over Time [F(3,56)=1.41, p=.25]. There was no statistically significant main effect for Time [F(3,56)=2.47, p.12], but the interaction between Time and Orientation was marginally significant [F(3,56)=3.89, p=.05]. Finally, no significant interaction was observed between the 4 Outcomes, Time and Occupational orientation [F(3,56)=.41, p=.75]. Most students considered the Physical activity and fitness goal as the prevailing one. Generally, the second year of the undergraduate program does not seem to influence students’ beliefs, but one main trend seems to arise. Students with a teaching orientation reinforced their beliefs towards all 4 expected outcomes, while coaching oriented students’ beliefs did not alter or declined. Teaching oriented students probably incorporate more efficiently messages retrieved from their undergraduate program.